Literature as a Means of Communication: A Beauvoirian Interpretation of an Ancient Greek Poem - Ruonakoski, Erika (Sapere Aude, 2013)
The aim of this article is twofold. Firstly, it explicates Simone de Beauvoir’s views on literature as a means of communication. Secondly, it draws from her theoretical framework to illuminate the discussion on mortality and death in a poem by an ancient Greek woman epigrammatist, Anyte. These two goals are combined by the fact that for Beauvoir one of the most important tasks of literature was to break down the solitude of human existence by sharing the most intimate and painful experiences, such as the death of our loved ones. I will argue that Beauvoir’s insights help us understand literature and its most profound, communicative dimension. On the other hand, taking the Beauvoirian framework to a field unknown to it before will elucidate its potential as a tool for literary analysis. Finally, the dialogue the article establishes between two women authors, Beauvoir and Anyte, will provide us with a more detailed understanding of the meaning of death in human existence and in literary communication. O objetivo desse artigo é duplo. Primeiramente, explica as visões de Simone de Beauvoir sobre a literatura como um meio de comunicação. Em segundo lugar, baseia-se em sua estrutura teórica para elucidar a discussão sobre mortalidade e morte em um poema de uma epigramatista da Grécia antiga, Anyte. Essas duas metas se combinam pelo fato de que, para Beauvoir, uma das tarefas mais importantes da literatura é abater a solidão da existência humana ao compartilhar as experiências mais íntimas e dolorosas, como a morte de nossos entes queridos. Argumentarei que os insights de Beauvoir nos ajudam a entender a literatura e sua dimensão mais profunda de comunicação. Por outro lado, levando a estrutura beauvoiriana para um campo desconhecido a ela até então, elucidarei seu potencial como uma ferramenta para a análise literária. Por fim, o diálogo que o artigo estabelece entre duas autoras, Beauvoir e Anyte, provê-nos com um entendimento mais detalhado do sentido da morte na existência humana e na comunicação literária.